Situation Report: Czechoslovakia, 19 December 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Federal Assembly Session The Munich Agreement: Hints at Willingness to Compromise? Intellectuals Seek Court Order for Return of Documents Committee of the Czech Writers' Union Meets